Teaching through Images : Imagery in Greco-Roman Didactic Poetry - Clay, Jenny Strauss,; Vergados, Athanassios, (Mnemosyne, Supplements ;, 2022)
In ancient didactic poetry, poets frequently make use of imagery - similes, metaphors, acoustic images, models, exempla, fables, allegory, personifications, and other tropes - as a means to elucidate and convey their didactic message. In this volume, which arose from an international conference held at the University of Heidelberg in 2016, we investigate such phenomena and explore how they make the unseen visible, the unheard audible, and the unknown comprehensible. By exploring didactic poets from Hesiod to pseudo-Oppian and from Vergil and Lucretius to Grattius and Ovid, the authors in this collective volume show how imagery can clarify and illuminate, but also complicate and even undermine or obfuscate the overt didactic message. The presence of a real or implied addressee invites our engagement and ultimately our scrutiny of language and meaning.